A VOLTAGE SENSITIVITY INDEX APPLICATION FOR POWER SYSTEM LOAD SHEDDING CONSIDERING THE PRIMARY AND SECONDARY GENERATOR CONTROLS - Trong Nghia, Le; Tran Tung, Giang; Quyen Huy, Anh; Phan Thi Thanh, Binh; Nguyen Thai, An; Pham Hong, Hau (Institute of Advanced Engineering and Science)
This paper proposes a method for calculating the minimum amount of power load needed to shed and distributing it for each load bus in order to recover the frequency and voltage back to the allowable range. Based on the consideration of the primary control of the turbine governor and the reserve power of the generators for secondary control, the minimum amount of load shedding was calculated in order to recover the frequency of the power system. Computation and analysis of Voltage Sensitivity Index (VSI) of the load bus to prioritize distribution of the amount power load shedding at these positions. The lower the load bus have the Voltage Sensitivity Index (VSI), the higher the amount of load shedding will shed and vice versa. With this technique, frequency and voltage value are still within allowable range, and a large amount of load shedding could be avoided, hence, saved from economic losses, and customer service interruption. The effectiveness of the proposed method tested on the IEEE 37 bus 9 generators power system standard has demonstrated the effectiveness of this method.